Development of a Measurement System for Fission Gases Released from Spent Pressurized Water Reactor Fuel during Heat Treatment - Lee, Jung-Won; Park, Jang-Jin; Park, Geun-Il (Asian Journal of Chemistry, 2012)
For an evaluation of the release behaviour of fission gases during DUPIC (direct use of spent pressurized water reactor fuel in CANDU reactors) fuel fabrication processes, a g-ray on-line monitoring system was developed. The system is composed of a g-spectrometer located outside a hot cell and a tubular furnace located inside the hot cell. The g-detector was aligned with the sample located in the tubular furnace in the hot cell to measure the radioactivity of the sample through the hole of the shield plug in the hot cell wall. Using this monitoring system, a quantitative analysis of the release behaviour of fission gases was conducted during heat treatment of spent pressurized water reactor fuel. It was observed that Cs-137 was not released during oxidation at 500 ºC, but almost 99 % of Cs-137 was released during sintering at 1800 ºC. Verification test of the measuring system was performed by comparing experimental results with chemical analysis data.